Perioperative outcomes of robot‐assisted nephroureterectomy for upper urinary tract urothelial carcinoma: a multi‐institutional series. (23rd July 2013) - Pugh, Joseph; Parekattil, Sijo; Willis, Daniel; Stifelman, Michael; Hemal, Ashok; Su, Li‐Ming
<x xml:space="preserve">Abstract</x> Objective To review a multi‐institutional series of robot‐assisted nephroureterectomy (RANU) for management of upper urinary tract urothelial carcinoma (UUTUC) with respect to technique and perioperative outcomes. Patients and Methods Between May 2007 and July 2011, 43 RANU were performed at three institutions for UUTUC with review of perioperative outcomes. A three‐ or four‐armed robotic technique was used in all cases based on surgeon preference and the entirety of all procedures was performed using the robot‐assisted technique. Single and two robot‐docking techniques are described. Results The mean (range) operating time was 247 (128–390) min, blood loss was 131 (10–500) mL and the median (range) length of stay was 3 (2–87) days. Pathology was pTa in nine patients, pT1 in 14 patients, pT2 in three patients, pT3 in 15 patients and pT4 in two patients. Lymph node dissection was performed in 22 patients (51%) with a mean (range) lymph node count of 11 (4–23). There were six postoperative complications: bleeding requiring a blood transfusion (grade II), splenic bleeding (grade IV), two cases of pneumonia (grade II) and two cases of rhabdomyolysis (grades II and IV). Nine recurrences (six bladder, two within the retroperitoneum and one in the contralateral collecting system) have been found to date on routine surveillance with a mean follow‐up of 9 months. Conclusions RANU is a feasible alternative to laparoscopic and open techniques. Particular steps of the operation including sutured closure of the cystotomy and regional lymphadenectomy are facilitated with the use of robot‐assisted surgery. Long‐term outcomes are necessary to assess the relative efficacy of these approaches to more established techniques; however, early perioperative outcomes appear promising.